Reply to comment by Yangang Liu et al. on "Cloud droplet spectral width relationship to CCN spectra and vertical velocity". Issue 4 (9th January 2014) - Hudson, James G.; Noble, Stephen
Key Points Standard deviation of droplet spectra is better than relative dispersion for determining the contribution of spectral width to cloud radiative properties